The Factors Predicting Post-Hospital Discharge Chest Pain Status Among Acute Coronary Syndrome Patients During The First Year - Supanam, Suthat; Liangchawengwong, Sunthara; Piyayotai, Dilok (Journal of The Royal Thai Army Nurses, 2020)
This predictive correlation research was to determine the factors for predicting post-hospital discharge chest pain status among acute coronary syndrome patients during first year. The samples were the acute coronary syndrome patients who following at outpatient department of medicine of Thammasat University Hospital. Data were collected from September, 2018 to January, 2019. The sample consisted of 181 participants, all of whom completed five sections of a self-administered questionnaire comprising the following: 1) Sociodemographic and Health Status Questionnaires 2) Post-ACS Stress Questionnaires 3) Sleep Quality Questionnaires 4) Post -ACS Self-management Behaviors Questionnaires and 5) The Seattle Angina Questionnaire. Data were analysed using descriptive statistic, Chi-square test, Spearman’s rank correlation coefficient, Pearson’s product correlation coefficient, and Stepwise multiple regression analysis. The results found that the mean scores of participant’s chest pain status were moderate level. By examining the stepwise multiple regression for predicting chest pain status, it was found that the factors that could predict this status included age, body mass index, occupation, ACS diagnosis, self-management behaviours, sleep quality, and smoking. All seven variables were able to predict chest pain status at 43.1 percent. Based on the findings, the results from this study provide useful information for developing programmes to prevent chest pain in this group in the future.